Behavioral intentions of Saudi female students in the College of Computer Science and Engineering at Taibah University in Saudi Arabia toward using mobile computer devices in their learning - Alnehari, Naif Nasser (My University, 2025)
The Kingdom of Saudi Arabia is making crucial progress and development in all fields, including education, as it develops higher education to compete globally. Among these strategies is the effective integration of technology into the educational environment, a key goal of Vision 2030. The spread of mobile computer devices among students has proven effective in student learning. However, there is still a lack of studies about the effectiveness of these mobile computer devices in higher education, especially among Saudi female students. Therefore, processes are involved before integrating any technology into the educational environment; one is to understand students' acceptance of these devices in their learning journey. Thus, the purpose of this study is to predict the behavioral intention of Saudi female students in the College of Computer Science and Engineering at Taibah University in Saudi Arabia to learn with mobile computer devices based on the constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003). This study employed a quantitative, non-experimental survey design to collect data. The number of responses received was 134; 127 were valid. The multiple linear regression analysis was administered to answer the research questions. The results revealed that effort expectancy and social influence were significantly associated with the female Saudi students' behavioral intentions toward using mobile computer devices in their learning ([beta] = 0.444, p < 0.001; [beta] = 0.174, p = 0.033). Performance expectancy had no statistically significant relationship with the behavioral intentions of Saudi female students regarding the use of mobile computer devices ([beta] = 0.108, p = 0.232). In addition, multiple linear regression results were presented, showing that the model accounted for 39% of the variance in the behavioral intentions of Saudi female students regarding the use of mobile computer devices in their learning. The current study also revealed some challenges students face when using mobile computer devices for learning. These include classroom infrastructure issues, such as limited Internet access and low-quality hardware, as well as battery and device performance problems when downloading files and applications. Additionally, some educational websites and content were incompatible with these devices. Based on these findings, the current study provides recommendations for future research and for improving educational practices when integrating mobile computer devices.
Keywords: Mobile computer devices; Mobile learning; Mobile technology; Behavioral intention; Taibah University; Saudi female students